ANALISA PERBANDINGAN SIMPANGAN STRUKTUR GEDUNG SET BACK TANPA DINDING GESER DAN PEMODELAN LETAK DINDING GESER DI ZONA GEMPA TINGGI - Tondi Amirsyah Putera; Fiqih Hidayat (Portal: Jurnal Teknik Sipil, 2017)
The high-rise building structure is prone to lateral forces, mainly due to the force generated by the earthquake. In calculating the multilevel building structure there are 2 ways, namely with Open Frame and Open Frame combination with shear wall. The shear wall is a wall that acts as a stiffener and is also a core wall for rigging entire buildings designed to withstand shear forces, lateral forces caused by earthquakes. so that the horizontal deformation (deflection) becomes small. The analysis used in this research is spectrum response analysis based on SNI 1726: 2012. This research has 3 model of set back building which will be reviewed, that is the model of set back building with special moment frame system, the model of backyard building with shear wall of each side and model of set back building with shear wall only on one side. All load inputs, stiffness and structural dimensions are the same, which differ only the special moment frame system model and the sliding wall placement used. This building has a height of 39.5 meters (10 floors). Based on this data it shows that the deviation result with the deviation modeling for the model is 0.075 m for the X and 0.064 direction for the Y direction for model 2 0.051 m for the X and 0.050 m directions for the Y direction and for model 3 is 0.074 m for the X and 0.048 for direction Y.Keywords: Set Back, Irregular Building, Drift Story, Shear Shear, Shear Wall, Special Moment Resume Frame.